Sexual and reproductive health of CDC plantation camp residents: a focus on unmet need for family planning among women in union - Agbor Nathan Emeh; Ngouakam Hermann; Elvis Asangbeng Tanue; Nsagha Shey Dickson (BMC, 2023)
Abstract Background Sexual and reproductive health is crucial to a normal and healthy female life. However, little interest has been placed on this subject particularly in the resource-limited settings of Cameroon. The study assessed the sexual and reproductive health of women in union, resident in the Cameroon Development Corporation (CDC) plantation camps, Cameroon. Methods This was a cross-sectional study carried out from December 2019 to February 2020 in which a multi-stage sampling was applied in two purposively selected CDC plantation camps (Tiko and Penda Mboko). Out of the 16 clusters making up the camps, 8 were randomly selected using simple balloting. The main street junctions of the sampled clusters were identified and a direction of sampling randomly chosen. All houses left to the data collectors were sampled for eligible participants (one participant per household) and data were collected using validated interviewer-administered questionnaires. The number of participants per cluster was proportionate to population size of cluster. Data was analysed using SPSS 16 and statistical significance was set at p < 0.05. Regression analysis was used to determine predictors of unmet need for family planning. Results Out of the 414 participants included, primary education was the highest level of education for a majority (43.0%). Most of the participants (44.7%) earned between 44.5-89.0USD/month. Relatively high proportions of some sexual and reproductive indicators like early sexual contacts (before 15 years) [87(21.0%)], grand multiparity [41(9.9%)], and abortion ≥ 3 [8(1.9%)] were recorded in the study. Two hundred and seventy-eight (278) participants (67.1%) [95%CI:62.4-71.7] used contraceptives and 90 (21.7%) [95%CI:17.9-26.0] had an unmet need for family planning with 3 major reasons for non-use of contraception among them being fear of side effects, discouragement from the partner, and lack of sufficient information on contraception. Of the different predictors of unmet need for family planning assessed, nulliparity/primiparity were protective for unmet need, and this was statistically significant (AOR = 0.284[0.086-0.934]). Conclusion The sexual and reproductive health of CDC plantation camp residents is poor, and a health intervention is needed to improve it.